2006
DOI: 10.1021/la062469z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between a Cationic Protein and a Cationic Fluorosurfactant

Abstract: Surface tension, 19F and 1H NMR spectroscopy, and cryotransmission electron microscopy are used to characterize the state of association in aqueous solutions of a fluorosurfactant CF3(CF2)nSO2NH(CH2)3-4N(CH3)3+ I- (n = 8, 6) with and without lysozyme added. In the absence of lysozyme, we find monomers, small aggregates, and large vesicles to coexist, with the individual fluorosurfactant molecules exchanging slowly (>1 ms) among those states. When both lysozyme and fluorosurfactant are present in the solution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Fluorosurfactants are a class of surfactants with partially perfluorinated tails which are hydrophobic as well as lipophobic. Recently, they have become a interesting topic due to their higher surface activity and chemically stability than their hydrocarbon analogues in acid or alkaline solutions. Nonionic fluorosurfactants (F(CF 2 CF 2 ) 1–7 CH 2 CH 2 O(CH 2 CH 2 O) 0–15 H, Zonyl FSN) are commercially available with a polyoxyethylene chain in their hydrophilic part and a fluorocarbon chain at the hydrophobic part. Zu and co-workers concluded that the adsorption of FSN at hydrophilic electrodes was stronger than that of their hydrocarbon analogues. , Recently, Tang et al utilized scanning tunneling microscopy (STM) measurement to validate the formation of FSN SAMs on Au surface through physical interaction between its hydroxyl groups at the end of the hydrophilic part .…”
Section: Introductionmentioning
confidence: 99%
“…Fluorosurfactants are a class of surfactants with partially perfluorinated tails which are hydrophobic as well as lipophobic. Recently, they have become a interesting topic due to their higher surface activity and chemically stability than their hydrocarbon analogues in acid or alkaline solutions. Nonionic fluorosurfactants (F(CF 2 CF 2 ) 1–7 CH 2 CH 2 O(CH 2 CH 2 O) 0–15 H, Zonyl FSN) are commercially available with a polyoxyethylene chain in their hydrophilic part and a fluorocarbon chain at the hydrophobic part. Zu and co-workers concluded that the adsorption of FSN at hydrophilic electrodes was stronger than that of their hydrocarbon analogues. , Recently, Tang et al utilized scanning tunneling microscopy (STM) measurement to validate the formation of FSN SAMs on Au surface through physical interaction between its hydroxyl groups at the end of the hydrophilic part .…”
Section: Introductionmentioning
confidence: 99%